(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In our nation, individuals just not contemplate themselves for good health and pleasure, yet additionally appeal to God for network’s prosperity. When we talk about the good health, right away the expressions of medications come into our brains, these prescriptions consistently require curing ailments and expanding the life expectancy healthier. The present proposition work comprises of the improvement of Quantitative Structure Activity Relationship models for antiviral drug molecules by performing in silico analysis in particular topomer CoMFA, HQSAR and Hansch. The models have been created utilizing biological activities and the fitting arrangement of parameters. The noteworthy parameters to clarify the biological activities have been acquired with the assistance of the proper factual strategies, for example, Multiple Linear Regression Analysis and Halfway Least Square Regression Analysis. Along these lines the impact of basic parameters of drugs on their biological activities are featured during their connections with receptor locales.